Modeling the influence of photochemistry on hydrogen peroxide concentrations in an Arctic snowpack. Issue 11 (10th June 2013) - Hullar, Ted; Anastasio, Cort
Abstract : [1] While laboratory experiments suggest that hydrogen peroxide (HOOH) on polar snow grains should be completely photolyzed during summer, field measurements show a continuous, multiyear record of HOOH in the snowpack. To understand this discrepancy, we apply a snow parcel model to follow HOOH in the snowpack at Summit, Greenland. Taking into account snowfall and variations in actinic flux, we evaluate the impact of three photochemical factors on HOOH preservation: the quantum efficiency of HOOH photodestruction, HOOH recycling through organic compounds, and HOOH photoproduction from snowpack chromophores. We find that 60%–100% of deposited HOOH is preserved in the first year, with less preservation of HOOH deposited during summer, and that the OH produced from HOOH photolysis likely contributes strongly to transforming snowpack bromide and organic compounds. Our findings suggest that photochemistry plays an important role in HOOH loss in snows at Summit and other polar sites, complementing temperature‐dependent physical processes. Key Points: We modeled one year of hydrogen peroxide photochemistry in a polar snowpack Photolysis can destroy up to 40% of HOOH deposited in summer Photochemistry complements physical mechanisms to control HOOH concentrations